Examining the Risks of Engaging in Population-based Surveys on Violence: Follow-up Study of the Individual Deprivation Measure in South Africa. (July 2021) - Sikweyiya, Yandisa; Mahlangu, Pinky; Dartnall, Elizabeth; Suich, Helen
In the South African Individual Deprivation Measure, the individual survey, included questions about two potentially highly sensitive topics—individuals' experience of violence and their control over personal decision making. In-depth follow-up interviews were conducted with 105 consenting survey participants to determine whether participating in the survey resulted in negative impacts for individuals, particularly in relation to these two topics. Several participants found that being asked about their experiences resurfaced painful memories, but we did not find any evidence that the approach of surveying every eligible individual in the dwelling resulted in any form of harm for the survey participants.